Early postoperative tumor marker responses provide a robust prognostic indicator for N3 stage gastric cancer. Issue 32 (August 2017) - Zhang, Qingrui; Qu, Hui; Sun, Guorui; Li, Zhiqiang; Ma, Shuzhen; Shi, Zhenxing; Zhao, Ensheng; Zhang, Hao; He, Qingsi
Abstract : Abstract: The clinical significance of tumor markers after radical gastrectomy has not been well characterized. The purpose of this study is to evaluate the prognostic value of early postoperative tumor marker normalization in N3 stage gastric cancer (GC) patients. A total of 259 N3 stage GC patients with preoperatively elevated carcinoembryonic antigen (CEA, >5 ng/mL) or carbohydrate antigen 19-9 (CA19-9, >37 U/mL) levels underwent radical gastrectomy were analyzed retrospectively. Early postoperative tumor marker response was considered as a normalization of CEA or CA19-9 levels 4 weeks after surgery. The disease-free survival (DFS) and overall survival (OS) were analyzed. N3 stage GC patients were divided into N3a (n = 157) and N3b (n = 102) groups according to the 8th TNM stage system. Early tumor marker response was identified in 96 of 157 N3a patients (61.15%) and 57 of 102 N3b patients (55.88%). In N3 stage GC patients with a tumor marker response, significant increase was observed in both DFS (25.2 months vs 12.5 months, P  < .001) and OS (32.5 months vs 18.5 months, P  < .001) compared with those without tumor marker response. N3b patients with a tumor marker response showed more favorable DFS (19.2 months vs 13.6 months, P  = .019) and OS (25.8 months vs 19.0 months, P  = .013) compared with N3a patients lacking a tumor marker response. Multivariate analysis revealed that early tumor marker response was an independent factor for DFS and OS in N3 stage GC, as well as for depth of invasion and metastatic lymph node rate ( P  < .05). Early postoperative CEA or CA19-9 normalization serves as a strong prognostic indicator in N3 stage GC. Both N3a and N3b patients with increased early postoperative tumor marker levels showed poor outcomes.